2016
DOI: 10.1007/s10072-016-2754-z
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in patients with essential tremor

Abstract: The aim of this study was to evaluate the autonomic function in patients with essential tremor (ET). Thirty-one adult patients with ET and 26 healthy controls were enrolled in the study. The electrophysiological evaluations of the autonomic nervous system function were performed by sympathetic skin response (SSR) and R-R interval variation (RRIV) tests. The mean latency of SSR in ET patients was significantly delayed compared with the controls (P = 0.01). The mean amplitude of sympathetic skin response was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Further, we observed cardiovascular‐related symptoms in patients with ET along with postural hypotension, excessive sweating, and swallowing disturbances, which might be related to autonomic disorders. Although a literature review did not reveal many related findings, previous self‐reported and objective studies have reported mild autonomic failure, especially regarding the cardiovascular and urogenital systems 31,32 . However, the pathogenesis of the sympathetic and parasympathetic dysfunction in patients with ET remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Further, we observed cardiovascular‐related symptoms in patients with ET along with postural hypotension, excessive sweating, and swallowing disturbances, which might be related to autonomic disorders. Although a literature review did not reveal many related findings, previous self‐reported and objective studies have reported mild autonomic failure, especially regarding the cardiovascular and urogenital systems 31,32 . However, the pathogenesis of the sympathetic and parasympathetic dysfunction in patients with ET remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…The authors found a higher prevalence of abnormal SSR test results in ET patients than controls, indicating sympathetic dysfunction in these patients. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 However, evidence on the association of ET with rapid eye movement (REM) sleep behavior disorder (RBD) 2 or autonomic symptoms remains conflicting. 2 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Recent autonomic symptom questionnaire-based analyses and sympathetic skin response-based studies have shown a variety of autonomic dysfunctions associated with ET, especially in the fields of cardiovascular and urogenital diseases (90)(91)(92).…”
Section: Heart Rate Variabilitymentioning
confidence: 99%